Menggali Potensi Vegetasi Adaptif Dan Benilai Ekonomi Pasca Erupsi Gunung Marapi Di Nagari Canduang Koto Laweh Kabupaten Agam - Alexander Syam; Tiara Suci Ramadani; Nila Sari (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2025)
On December 3, 2023, at 2:54 PM WIB, an explosive eruption occurred with an eruption column height of approximately 3,000 meters above the summit (5,891 meters above sea level) and recorded on a seismograph with a maximum amplitude of 30 mm and a duration of 4 minutes 41 seconds. The eruption column was observed to be gray with thick intensity leaning towards the east. The eruption was also accompanied by pyroclastic flows to the north with a sliding distance of 3 km from the summit. A number of commodity fields such as rice, sugar cane, and other crops were recorded to be covered in volcanic ash. "A total of 2,141 hectares of agricultural land was covered by volcanic ash from Mount Marapi. The affected crops were rice, sugar cane, and horticultural crops. Of the approximately 2,000 hectares, approximately 1,100 hectares were rice, approximately 700 hectares were sugar cane, and approximately 340 hectares were horticultural crops. Horticultural crops were the most severely affected. Based on observations and research, the most suitable crops for post-eruption Mount Marapi are annual agroforestry crops. Keywords: Adaptive Vegetation; Post-Eruption; Mount Marapi